HYDROCHEMICAL EVALUATION AT LAMBARI RIVER, SÃO JOSÉ DOS CAMPOS (SP), BRAZIL - Lee, Isabela G. [UNESP] (2021)
This paper describes a hydrochemical study held at Lambari river, a tributary of Paraíba do Sul river that is located at São José dos Campos city, São Paulo State, Brazil. Such drainage crosses the installations of the Henrique Lage Oil Refinery (REVAP), allowing identify possible pollutants inputs on the water resources due to the development of the industrial activities taking place there. Two sampling campaigns were realized in the wet seasons of 2019 and 2020 aiming to collect rainwater and surface water samples in 32 monitoring points. Physicochemical parameters (temperature, pH, redox potential (Eh), electrical conductivity (EC), turbidity and dissolved oxygen), as well hydrochemical parameters (Na+, K+, Ca2+, Mg2+, alkalinity, Cl-, NO3 -, SO4 2-, surfactants, tannin–lignin, benzene, toluene, ethylbenzene and xylene (BTEX) and other organic compounds) and dissolved radon (222Rn) provided a robust dataset for understanding the major processes related to modifications in the water quality. Direct relationship was found between EC and total dissolved solids (TDS) in the waters of Lambari river as often described elsewhere. Sodium and chloride were the two dominant ions that justified the EC–TDS relationship. Additionally, both EC and TDS as well correlated significantly with alkalinity (bicarbonate). The rainwater is impoverished in the dissolved constituents relatively to the surface waters, which acquire them during the rainfall interactions with the soil covers/rock surfaces or anthropogenic inputs into the Lambari river channel. The Piper diagram highlighted that the hydrochemical facies of rainwater and surface waters are the same, i.e. sodium bicarbonate. The Gibbs boomerang diagrams suggested dominant influence of the dilution effects by rainwater in the hydrochemical composition of the surface waters of Lambari river. Dissolved oxygen and radon correlated significantly, while the analytical data did not indicate changes in the concentration of BTEX and other organic compounds in the waters of Lambari river due to the industrial activities developed by REVAP.